The Comparison of Functional Outcomes Between Supraglottic Horizontal Laryngectomy and Supracricoid Partial Laryngectomy - Suat Bilici; Artunc Kaan Turanoglu; Ozgur Yigit; Ecem Sevim Longur (Journal of Otolaryngology Advances, 2017)
Objectives The aim of this study was to compare the functional outcomes (including swallowing, respiration and phonation) of supraglottic horizontal laryngectomy (SGHL) and supracricoid partial laryngectomy (SCPL). Methods The clinical and pathological data were evaluated for 36 previously untreated patients who were diagnosed with laryngeal carcinoma and underwent SGHL or SCPL at the Department of Otorhinolaryngology-Istanbul Training and Research Hospital from 2010 to 2016. Removal of the nasogastric tube, decannulation and hospitalisation times were recorded in both groups and postoperative complications were noted. Results The SGHL group contained 15 patients and the SCPL group contained 21 patients (14 cases of cricohyoidoepiglottopexy (CHEP) and 7 cases of cricohyoidopexy (CHP)). The mean age of the subjects was 57.4 years in the SGHL group, and 59.7 in the SCPL group. Patients in the SGHL group were decannulated after 65.2 days, whereas the average decannulation time was 72.6 days in the SCPL group. This difference in decannulation time between the groups was not statistically significant (p>0.05). The mean hospitalisation time was 23 days, with no statistically significant difference between the groups (>0.05). The nasogastric tube was removed from the patients after 37.9 days in the SGHL group and after 35.8 days in the SCPL group. No statistically significant difference was determined in the time to start feeding between the groups (p>0.05). Surgical wound infection, the occurrence of pharyngo-cutaneous fistulas and rupture of the pexy sutures were complications. Conclusion Functional outcomes of SCPL were similar to those of patients who underwent SGHL. The preservation of the hyoid bone is the most important consideration for preserving the swallowing function.
Keywords: Supraglottic laryngectomy